ANALISIS KUALITAS MADU KELULUT (Trigona sp) DARI DESA MANGKAUK KECAMATAN PENGARON KABUPATEN BANJAR - Rama Ridoni; Rosidah Radam; Fatriani Fatriani (Universitas Lambung Mangkurat, 2020)
Aim of the was analyze quality of kelulut (Trigona sp) generated from the village of Mangkauk sub-district of Banjar Regency is a wide including moisture content, ash levels, reducing sugars, sucrose, sugar levels of acidity, solids is insoluble in water, lead, copper and arsenic. This research procedure using the honey quality test based on SNI 01-3545-2004. Research on the quality of honey owned by honey farmers from Mangkauk Village fulfills SNI 01-3545-2004, i.e. the levels of sucrose, solid is soluble in water, lead, copper, and arsenic, the results of the analysis of honey that does not meet SNI (01-3545-2004), the moisture content, reducing sugar levels and acidity content.Keywords: The qualities of honey kelulut; the water level; Acidity levels reducing sugar